Software Design and Development of Beverage Vending Machine System Using ARM Architecture with LPC2148 - Sanket Suresh Naik Dessai (Institute of Advanced Engineering and Science, 2015)
Beverage vending machine systems are becoming popular in the Indian market.These systems are today available in Indian MNCs and some top rated restaurants and hotels.In most systems the operation are carried manually by the operator in which the billing and change making is carried out by the owner who runnig the shop or restaurant.In India tea and coffee habits were cultured by the colonial rule of the British and the Portuguese,even tody the colonial rule had been over but the habits of tea and coffee beverage consumptions becomes as the routine daily life.Hence there is a need to understand beverage vending machine systems to serve the Indian Market. In this paper,a critical analysis of requirement has been carried out and the system design had been arrived at.The system requirement demand an ARM based controller for better system performance.To meet the system performance criteria and richest of peripherals an LPC2148 with low cost had been selected.The system is more efficient to analyse the change making and the identification had been carried out using the motors,LCDs,water heater,solenoid valve,money box,change making and dispensing unit. The system is tested and validated for the specified test cases.The milk motor run for 10 rotations to drive 200 milligrams of milk powder to the container to make to tea or coffee beverage.In this system a stepper motor had been used can be replaced by using dc motors to avaoid power losses.In future an ATM or credit card based payment system can be incorporated to these systems.